Endoscopic Management of Double Esophageal Perforation by Ingested Foreign Body Using Over-the-Scope Clip: A Case Report - Debnath, Prasanta; Rathi, Pravin; Nair, Sujit; Udgirkar, Suhas; Chandnani, Sanjay (Journal of Digestive Endoscopy, 2020)
Esophageal perforation is a life-threatening condition with a high mortality rate. First described around 300 years ago, management of this fatal condition has emerged from surgical to endoscopic modalities with much less morbidity and mortality when instituted early. We present this case of 55-year-old male, with double esophageal perforation by meat bone, perforating lower esophageal wall, leading to localized hydropneumothorax on right side with mild bilateral pleural effusion managed endoscopically with Over-the-Scope-Clip. Endoscopic management of esophageal perforation has been well mentioned in literature, without any mention of such management in case of double esophageal perforation. Surgery with or without endoscopy remains the main stay of management of such cases.
Keywords: esophageal foreign body; endoprosthesis; endoscopy; esophageal perforation